Działalność kół PPR i PZPR w MO województwa gdańskiego w latach 1945–1949 - Sywula, Michał (Komunizm: System - Ludzie - Dokumentacja, 2023)
The article presents the activity cells PPR and then PZPR in the Milicja Obywatelska (Citizens' Militia) over the years 1945-1949. It described the process of organizing and functioning the party executive and the Provincial Committee PPR in the KW MO (Regional Headquarters of Citizens' Militia) in Gdansk. The article also includes information on the membership militian officers to political parties.